The Impact of Community Disadvantage on the Relationship between the Family and Juvenile Crime - Hollist, Dusten; Altheimer, Irshad; Schaible, Lonnie M. (Journal of research in crime and delinquency, 2006)
Prior research on the family has identified many variables significantly associated with criminal involvement including such things as parental supervision and discipline and the quality of the parent child relationship. However, little attention has been devoted to the possibility that the effects of these variables on crime depend on characteristics of the social context in which a family resides. Using data from a national sample of adolescents, the authors examined how the effects of key family variables depend on two indicators of a community's level of disadvantage: its objective level of community poverty (as indicated by U.S. census data) and its perceived inadequacy as a place to raise children (as rated by parents). The analysis suggests that community disadvantage significantly amplifies the effects on crime of problems in the family environment. The implications of this conclusion for criminological theory and future research on the causes of crime are addressed. [ABSTRACT FROM AUTHOR]